Digital twin and men's underwear design. (December 2018) - Cheng, Z; Kuzmichev, V E
Abstract: Based on 3D body scanning technology, KES properties of real knitted materials, new body measurements for digital twin generating, we developed the virtual method of men's underwear try-on. The results show that by means of virtual software 3D CLO we can simulate well the body characteristic, the underwear structure, the knitted material elongation, and the compression pressure distribution. New underwear design can have a good presentation in customization and mass production.